Ictal atrial fibrillation during focal seizures: a case report and literature review. Issue 3 (17th July 2019) - Basili, Luca M.; Morano, Alessandra; Fattouch, Jinane; Fanella, Martina; Albini, Mariarita; Avorio, Federica; Irelli, Emanuele Cerulli; Manfredi, Mario; Urani, Claudia; Strano, Stefano; Giallonardo, Anna T.; Di Bonaventura, Carlo
ABSTRACT: Cardiac arrhythmias are a common but often overlooked symptom that occur during or after epileptic seizures. The characterization of seizure‐related heart rhythm disorders could shed light on the functional organization of the so‐called "central autonomic network" and possibly on the pathophysiology of sudden death of epilepsy patients (SUDEP). Indeed, epileptic discharges may affect the heart through the involvement of cortical regions selectively driving autonomic functions. Ictal atrial fibrillation is an exceedingly rare phenomenon, usually associated with generalized tonic‐clonic seizures. Here, we report a case of paroxysmal atrial fibrillation as a core presenting feature of a focal non‐motor seizure in a 68‐year‐old man, at first misdiagnosed and treated for a typical cardiogenic arrhythmia. A brief literature review is included.